Impact of overlapping fungal infection on the occurrence and prognosis of carbapenem-resistant gram-negative bacilli infection - Li, Jiahuan; Liu, Yushan; Xu, Tingting; Ma, Hongling; Zhang, Qian; Xiong, Lijuan (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThe global threat of carbapenem-resistant gram-negative bacteria (CRGNB) infection is compounded by concurrent fungal infections, which present additional clinical challenges. This study aims to elucidate the impact of fungal infection on the occurrence and prognosis of CRGNB infection.MethodsWe conducted a retrospective, single-center, observational cohort study of 2,273 patients with CRGNB and/or fungal infection from January 2018 to April 2023. Binary logistic regression analysis and multivariable Cox proportional hazards regression model were used to determine risk factors for the occurrence and prognosis of patients with CRGNB or fungal infections. Survival analysis was performed to investigate the impact of fungal co-infection on mortality of total GRGNB and bacterial subclasses infections.ResultsFungal infection was a independent risk factor for CRGNB infection (OR=1.381, p=0.015), and similarly, GRGNB was associated with an increased risk of fungal infection (OR=1.542, p<0.001). Besides, males and individuals with a history of ICU admissions, invasive surgeries, malignancies, mechanical ventilation, drainage tubes, or exposure to cephalosporin/carbapenem antibiotics were found to be more susceptible to both types of infections. Compared to patients with only GRGNB infection, co-infections contributed to a higher risk of mortality. However, co-infections do not amplify mortality risk in patients with only fungal infection. Further analysis revealed a significant increase in mortality of patients with carbapenem-resistant Klebsiella pneumoniae or carbapenem-resistant Acinetobacter baumannii co-infections, but no change in mortality rates was observed with carbapenem-resistant Escherichia coli or carbapenem-resistant Pseudomonas aeruginosa. Interestingly, we found that fungi were detected significantly earlier than CRGNB (median: 9 days vs. 21 days, p<0.001).ConclusionsIn the current study, it was discovered that fungal infections preceded GRGNB infections and might contribute to the development of antibiotic resistance in some gram-negative bacteria, which ultimately leads to more severe clinical outcomes.